Quantum Dots-siRNA Nanoplexes for Gene Silencing in Central Nervous System Tumor Cells - Lin, Guimiao; Chen, Ting; Zou, Jinyun; Wang, Yucheng; Wang, Xiaomei; Li, Jiefeng; Huang, Qijun; Fu, Zicai; Zhao, Yingying; Lin, Marie Chia-Mi; Xu, Gaixia; Yong, Ken-Tye (Frontiers in Pharmacology, 2017)
RNA interfering (RNAi) using short interfering RNA (siRNA) is becoming a promising approach for cancer gene therapy. However, owing to the lack of safe and efficient carriers, the application of RNAi for clinical use is still very limited. In this study, we have developed cadmium sulphoselenide/Zinc sulfide quantum dots (CdSSe/ZnS QDs)-based nanocarriers for in vitro gene delivery. These CdSSe/ZnS QDs are functionalized with polyethyleneimine (PEI) to form stable nanoplex (QD-PEI) and subsequently they are used for siRNA loading which specially targets human telomerase reverse transcriptase (TERT). High gene transfection efficiency (>80%) was achieved on two glioblastoma cell lines, U87 and U251. The gene expression level (49.99 ± 10.23% for U87, 43.28 ± 9.66% for U251) and protein expression level (51.58 ± 7.88% for U87, 50.69 ± 7.59% for U251) of TERT is observed to decrease substantially after transfecting the tumor cells for 48 hours. More importantly, the silencing of TERT gene expression significantly suppressed the proliferation of glioblastoma cells. No obvious cytotoxicity from these QD-PEI nanoplexes were observed over at 10 times of the transfected doses. Based on these results, we envision that QDs engineered here can be used as a safe and efficient gene nanocarrier for siRNA delivery and a promising tool for future cancer gene therapy applications.